CHA2DS2-VASc below 3 predicts low one-year ischemic stroke risk in postoperative atrial fibrillation after CABG. (14th October 2021) - Taha, A; Nielsen, S; Franzen, S; Rezk, M; Ahlsson, A; Friberg, L; Bjorck, S; Jeppsson, A; Bergfeldt, L
Abstract: Background: Ischemic stroke prevention is a major goal in patients with atrial fibrillation (AF). Neither the optimal risk assessment method, nor the risk-benefit-ratio of long-term use of oral anticoagulation (OAC) is, however, known in patients with new-onset AF (POAF) after cardiac surgery. Purpose: To explore the feasibility of using the CHA2DS2-VASc scoring system in predicting the one-year ischemic stroke risk in patients with POAF after coronary artery bypass grafting (CABG). Methods: All patients in Sweden with POAF after isolated CABG 2007–2017, with at least one year of follow-up, and without oral anticoagulation (OAC), were included in this observational, registry-based cohort study. POAF was defined as any new-onset AF during the index hospitalization for CABG. Primary endpoint was the one-year ischemic stroke risk at each step of the CHA2DS2-VASc score in POAF patients with at least one-year follow-up. Results: Out of 6368 POAF patients without OAC neither at hospital discharge nor before the occurrence of events, 4467 (70.1%) had at least one year follow-up with altogether 124 ischemic strokes within one year from discharge. The one-year risk for ischemic stroke was <1% for a CHA2DS2-VASc score <3, 1–2% for a CHA2DS2-VASc score 3, and >2% for a CHA2DS2-VASc score ≥4. The area under the receiver-operating-characteristic curve for predicting ischemic stroke was 0.67 (95% CI 0.64–0-69). Conclusions: The CHA2DS2-VASc score was suitable for predicting low risk for ischemic stroke during the first year after hospital discharge in patients with POAF after CABG. A risk <1% considered low was, however, observed at a considerably higher score than in patients with non-surgical/non-valvular AF described in previous studies. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish Heart-Lung Foundation (grant 20150587 and 20180560 to Anders Jeppsson)Region Västra Götaland (grant VGFOUREG-847811 to Anders Jeppsson and grant VGFOUREG-648981 to Amar Taha)